2021
DOI: 10.1515/zpch-2020-1749
|View full text |Cite
|
Sign up to set email alerts
|

Biochar caged zirconium ferrite nanocomposites for the adsorptive removal of Reactive Blue 19 dye in a batch and column reactors and conditions optimizaton

Abstract: Biochar caged zirconium ferrite (BC-ZrFe2O5) nanocomposites were fabricated and their adsorption capacity for Reactive Blue 19 (RB19) dye was evaluated in a fixed-bed column and batch sorption mode. The adsorption of dye onto BC-ZrFe2O5 NCs followed pseudo-second-order kinetics (R 2 = 0.998) and among isotherms, the experimental data was best fitted to Sips model as compared to Freundlich and Langmuir isotherms models. The influence of flow-rate (3–5 mL min−1), inlet RB19 dye concentration (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The plot q t versus t 1/2 could be linear only if intraparticle diffusion is involved in the sorption phenomenon, but if the line passes through the origin, then the intraparticle diffusion could be the rate determining step. When the plot did not pass via origin, it indicated boundary layer control at some extent and it showed that the intraparticle diffusion was not the only rate controlling step, but other kinetics models might also control the rate of sorption, all of which could operate simultaneously [32,57,59]. The findings of the intraparticle diffusion model are tabulated in Table S2 and Figure S3 (SI).…”
Section: Interparticles Diffusion Modelmentioning
confidence: 96%
See 1 more Smart Citation
“…The plot q t versus t 1/2 could be linear only if intraparticle diffusion is involved in the sorption phenomenon, but if the line passes through the origin, then the intraparticle diffusion could be the rate determining step. When the plot did not pass via origin, it indicated boundary layer control at some extent and it showed that the intraparticle diffusion was not the only rate controlling step, but other kinetics models might also control the rate of sorption, all of which could operate simultaneously [32,57,59]. The findings of the intraparticle diffusion model are tabulated in Table S2 and Figure S3 (SI).…”
Section: Interparticles Diffusion Modelmentioning
confidence: 96%
“…Additionally, the recent progress in their large-scale production makes them better for use as ideal organic and inorganic contaminants nanoadsorbents [28]. Extensive experimental work has been conducted on the adsorption of different dyes onto biochar-mediated nanocomposites, such as Congo Red dye [27], Reactive Red 24 [29], Tartrazine dye [30], Tartrazine dye [31], Reactive Blue 19 dye [32], Cr 3+ and Cd 2+ [33], Zn +2 and Fe +3 [34] and Tartrazine dye [35].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, aquatic flora and fauna have been negatively impacted, water has become unfit for human consumption, and public health is threatened [1][2][3]. The removal of azo dyes from industrial wastewaters is a critical environmental issue that has attracted substantial research attention in recent years [4].…”
Section: Introductionmentioning
confidence: 99%